Effect of Rates of Herbicide (Butachlor) on Weeds and Yield of Sunflower in Wukari Local Government Area in Taraba State, Nigeria - Zachariah Thom M.; Samuel Humphrey S.; Shinggu Chibiya P. (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Weeds are a major cause of yield and quality loss in sunflower (Helianthus annuus L.) production, making effective weed management essential. This study aimed to evaluate the effects of different butachlor-based weed-control regimes on weed suppression and grain yield of three sunflower varieties (Samsun1, Samsun3, and Local) at the Teaching and Research Farm of Federal University Wukari, Taraba State, Nigeria, during the rainy season. The experiment was laid out in a randomized complete block design with three replications, combining the three sunflower varieties with weed-management treatments that included butachlor applied at different rates, hoe weeding at 3, 6, and 9 weeks after sowing (WAS), and a weedy check. The results showed that butachlor at 1.5 kg a.i./ha, supplemented with hoe weeding at 6 and 9 WAS, produced significantly lower weed infestation, higher weed-control efficiency, and the highest grain yield per plot, with Samsun1 outperforming Samsun3 and the Local variety under this regime. This treatment was followed in effectiveness by butachlor at 1.0 kg a.i./ha and by sole hoe weeding at 3, 6, and 9 WAS, whereas the weedy check recorded the lowest grain weight per plot and the highest weed cover. The study concludes that integrating butachlor at 1.5 kg a.i./ha with supplementary hoe weeding at critical growth stages offers an effective strategy for reducing weed pressure and improving sunflower grain yield under the conditions of Wukari, thereby providing practical guidance for weed-management decisions in similar agro-ecological environments.